EXPANSION OF OBJECTIVES OF THE PRACTICAL APPLICATION OF TECHNICAL AUDIT AT RAILWAY TRANSPORT ENTERPRISES - Okorokov, A. M.; Bulakh, M. O. (Science and Transport Progress, 2017)
Purpose. The work is aimed to study, compare and summarize information on the current state and peculiarities of conducting technical audit in various branches of business in order to obtain the possibility of developing proposals for expanding the objectives of this procedure in railway enterprises. Methodology. In the course of the research there were used the methods of analysis and synthesis to study the content and basic provisions of scientific publications, normative legal acts of Ukraine, and other data on conducting technical audit in the field of industry, construction, gas extraction, electricity, marine and rail transport, followed by their comparison and generalization. Findings. Taking into account the positive experience of the audit carrying out in other sectors the article expands the goals of practical application of technical audit in railway transport enterprises. This envisages assessment of the current technical condition and the residual life of exploited vehicles and equipment of PJSC "Ukrzaliznytsia". As a result, there is an opportunity to detect and activate the reserves for improving the efficiency of railway transport enterprises, estimating and forecasting the costs for repair cycles and modernization, as well as for increasing the train safety level and improving investment attractiveness of the industry. Originality. The obtained results make it possible to broaden the concept of "technical audit" in railway transport, to define the purpose of its carrying out and the list of tasks. Application of the extended technical audit will provide an opportunity to receive objective information on the actual technical condition of the objects of the railway infrastructure, means of transport and equipment, and to use it for the formation of development programs as individual enterprises and the railway as a whole. Practical value. Expanding the goals of practical application of the technical audit at railway enterprises will increase the revenue part by identifying unused reserves, modernizing and obtaining investment, as well as reducing the expenditure part by minimizing the costs of eliminating the consequences of transport events, which is the cause of untimely identified technical risks.